Left atrial myxoma swinging like a ball valve thrombus: “The wrecking ball effect” (Indian Journal of Case Reports, 2021)
Left atrial myxoma is the most common benign primary tumor of the heart, more common in females, and often presents with non-specific symptoms with incidental detection in echocardiography. The bimodal mode of presentation of the left atrial myxoma is as follows: one group of patient’s presents with symptoms mimicking infective endocarditis and the other group of patient’s presents with symptoms of typical mitral stenosis. Large left atrial myxoma acting as a ball valve thrombus causing complete obstruction of the mitral valve and causing pulmonary venous hypertension with acute pulmonary edema has not been described in the literature so far. We report a rare case of large left atrial myxoma swinging like a ball valve thrombus across the mitral valve in a 76-year-old female presenting with acute pulmonary edema and desaturation. The patient underwent emergent surgical excision of the left atrial myxoma which relieved the pulmonary edema and desaturation as well. Left atrial myxoma being completely occlusive led to passive pulmonary venous hypertension and acute pulmonary edema: a rare phenomenon to be observed in a clinical scenario.